PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN SUBSEKTOR PERTAMBANGAN BATU BARA - Ni Komang Sinta Cahyani; Hendra Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study was to determine the effect of the Current Ratio, Debt to Equity Ratio, Return on Assets, Return on Equity, Net Profit Margin and Operating Profit Margin on stock prices at Coal Mining sub-sector company. The population used in this study are coal mining sub-sector companies listed on the Indonesia Stock Exchange from 2014-2020 and purposive sampling as the sampling method. The sample criteria that meet as many as 8 companies used in this study are from the financial statements of companies in the coal mining sub-sector listed on the Indonesia Stock Exchange. This study uses multiple linear regression method showing that the current ratio, debt to equity ratio, return on equity have an influence on stock prices. Current ratio, debt to equity ratio and roe have a negative effect to stock price because the higher liquidity also means the company have many idle funds. Higher DER and ROE also indicate the company less efficient in their activity.